Effects of homeopathic preparations on phenological development and control of insects and diseases of sweet pepper (Capsicum annuum L.) (Research, Society and Development, 2021)
The use of homeopathic preparations in horticultural crops allows reestablishing their homeostasis and reducing production losses caused by biotic and abiotic factors. This study aimed to assess the action of the homeopathic preparations Sulphur 30CH and Calcarea carbonica 30CH in the phenological development and control of insects and diseases that naturally affect sweet pepper. The experiment was conducted between 2018 and 2019 at the Research and Extension Center in Agroecology of the Experimental Farm Ressacada – UFSC, Florianópolis, Santa Catarina, Brazil. The experimental design consisted of randomized blocks in the field and a completely randomized design in a greenhouse and laboratory. The homeopathic preparations were chosen by the repertorization technique, based on symptoms observed in a previous crop test. The homeopathic preparation Sulphur enabled positive increases in the development of plants and production and diameter of fruits under field cultivation. Calcarea carbonica showed significant results at the height of plants grown in the greenhouse. The presence of caterpillars, ants, aphids, mites, fungi, and bacteria was found during cultivation. The homeopathic preparations showed no evident effects in reducing the populations of these pathogens in attacked plants and fruits, but they may favor the resilience of plants affected by these parasites, helping in the growth after the damage. Calcarea carbonica presented a trend of smaller quantities of fruits with signs of anthracnose. The application of the homeopathic preparations Calcarea carbonica and Sulphur on sweet pepper showed different effects depending on the growing environment.